Modelos de causalidad en Tomás de Aquino: análisis e interpretación en el contexto filosófico de la Expositio super librum de causis. - Martin De Blassi, Fernando Gabriel (Scripta Mediaevalia, 2024)
Through a historical, critical and hermeneutical analysis of both the sources and the specialized bibliography, the present work seeks to elucidate whether it is possible to evidence in Thomas Aquinas’s commentary on Liber de causis not only a historical reception but also a conceptual transformation of the models of efficient, exemplary and final causality that are operating in the textual plots collected by Aquinas (De divinis nominibus of Pseudo Dionysius Areopagita, the Elementatio Theologica of Proclus and the Liber de causis) in the problematic context of doctrinal disputes developed during the second half of the 13th century.